Production of molded products based on block copolymers (thermoplastic elastomers) - Kozhakhmet Мейрам; Salikhova Тоидык; Aitlesov Курмет (Рroblems of engineering and professional education, 2023)
In this work, TEP material was made. TEP is obtained on the basis of solid phase polymerization. TEP has very high technological properties. The studied material is suitable for the production of structural objects.